The Relationship between the Implementation of Mother's Care with the Length of the First and Second Stage of Childbirth in Maternal Maternity at Afisya Clinic, East Sambirejo Village, Deli Serdang Regency - Rina Marlina Hutasuhut (Journal of Midwifery and Nursing, 2022)
Abstract-Maternal care as one aspect of the 5 red threads really helps mothers to feel safe and comfortable during the delivery process. Maternal care during labor includes care given to mothers starting from stage I to stage IV. The implementation of basic maternal care or become the principle in providing maternal care in the delivery process includes providing emotional support, providing fluids and nutrition, flexibility for micturition and defecation, as well as infection prevention. Research Objectives: To determine the relationship between the implementation of maternal care and the length of the first and second stage of labor at the Afisya Clinic, East Sambirejo Village, Deli Serdang Regency in 2021. Research Methods: This study used an analytical descriptive design using a cross sectional approach. The population is all mothers who give birth at the Afisya line, East Sambirejo Village, Deli Serdang Regency in 2021 in May-August 2021, a total of 56 people. The sample was some mothers who gave birth at the Afisya Clinic, East Sambirejo Village, Deli Serdang Regency in 2021, a total of 49 people. Analysis of the data used is univariable by calculating the frequency in the form of a percentage of the variables studied and bivariable by calculating Chi-Square test statistics and processed using statistical products and service solutions (SPSS) 22. Research Results: maternal care with good category as many as 23 people or 46.9%. Maternal mothers who had a normal first stage of labor were 35 people or 69.5% and who experienced normal delivery were 39 people or 79.5%. The results of the chi-square analysis showed that there was a relationship between maternal care and the length of the first and second stage of labor with p=0.041 and p=0.043 (p<0.05). Conclusion: there is a relationship between maternal care and the duration of labor in the first and second stages.